2019
DOI: 10.3389/fimmu.2019.00795
|View full text |Cite
|
Sign up to set email alerts
|

Elevated CCL19/CCR7 Expression During the Disease Process of Primary Sjögren's Syndrome

Abstract: Primary Sjögren's syndrome (pSS) is a common chronic autoimmune disease characterized by a high prevalence of autoantibodies and lymphocyte-mediated exocrine gland damage. To enhance our understanding of the mechanisms underlying the progression of the disease and to discover potential biomarkers for the early diagnosis of pSS, we applied RNA sequencing to compare the gene expression patterns in minor salivary glands between pSS patients and non-pSS. A total of 293 differentially expressed genes (DEGs) were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 63 publications
(69 reference statements)
2
13
1
Order By: Relevance
“…To confirm the robustness of our sequencing results, we next compared the global transcriptomes of the control and pSS glands by utilizing RNA-sequencing (RNA-seq) datasets described here, to additional RNA-seq (Liu et al.) ( 49 ) and microarray array datasets (Min et al.) ( 50 ) that have been previously reported ( Figure 2 and Supplementary Figure S1 ).…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…To confirm the robustness of our sequencing results, we next compared the global transcriptomes of the control and pSS glands by utilizing RNA-sequencing (RNA-seq) datasets described here, to additional RNA-seq (Liu et al.) ( 49 ) and microarray array datasets (Min et al.) ( 50 ) that have been previously reported ( Figure 2 and Supplementary Figure S1 ).…”
Section: Resultsmentioning
confidence: 66%
“…We reasoned that this approach would address possible variations between the three datasets due to technical and experimental differences. Indeed, our analysis identified a number of genes common to all three datasets that have been previously demonstrated to play important roles in pSS pathogenesis including several members of the CXC chemokine family of cytokines including CXCL9, CXCL10, CXCL11, CXCL13 ( 15 , 51 , 52 ), members of the guanylate-binding protein family; GBP1 , GBP5 ( 49 , 53 , 54 ), as well as AIM2 ( 55 ), CD52 ( 56 ), and GZMK ( 57 ). To further confirm these results, we performed quantitative reverse-transcription polymerase chain reaction (qRT-PCR) using a subset of patient samples which were included in our RNA-seq analysis to examine the mRNA expression levels of a select number of candidate genes, several of which have been implicated in pSS pathogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the KEGG pathway enrichment analysis of common DEGs also suggested their relevance in the pathogenesis of pSS. Chemokine signaling pathway was essential for maintaining the function and interaction of T lymphocytes (Ward and Westwick, 1998), and cytokine CCL19 was identified as a biomarker of immunological activation in pSS with its chemokine receptor CCR7 in our other study (Liu et al, 2019). It has been reported that adhesion molecules, such as intercellular adhesion molecule-1 and vascular cell adhesion molecule-1, were indispensable factors for lymphocyte recruitment, glandular damage, and the development of vasculitis in pSS, indicating the importance of CAM pathway in the mechanism of pSS (Turkcapar et al, 2005).…”
Section: Discussionmentioning
confidence: 69%
“…Similarly, the branchpoint-site single-nucleotide polymorphisms rs17266594 and rs10516487 in the B cell scaffold protein with ankyrin repeats 1 (BANK1) gene have been testified to be associated with various autoimmune diseases including SLE (Guan et al, 2011), RA (Orozco et al, 2009), and SSc (Rueda et al, 2010). Moreover, in our other study, we had found that elevated CCL19/CCR7 expression in the salivary gland associated with anti-SSA/Ro antibody and IgG levels in pSS patients could serve as markers of immunological activation in pSS (Liu et al, 2019). Interestingly, although the inducible costimulatory molecule (ICOS), as a member of the CD28 family of coreceptor molecules, has been suggested to induce the difference of interleukin 17 (IL-17)-producing helper T cells (Th17 cells) and follicular helper T cells (Tfh cells), there are rare studies reporting the relativity between ICOS and pSS (Dong et al, 2001;Bauquet et al, 2009).…”
Section: Discussionmentioning
confidence: 83%
“…RNA-seq raw reads were processed in a similar manner as previously described. 53,54 Both 3 0 and 5 0 adapter contaminants were removed by Cutadapt, and the full-length reads were processed as FASTA format using an in-house pipeline. 55 After preprocessing, the quality of these reads was evaluated by FastQC and further visualized by SplicingViewer software.…”
Section: Data Preprocessingmentioning
confidence: 99%